The Transplantation of hBM-MSCs Increases Bone Neo-Formation and Preserves Hearing Function in the Treatment of Temporal Bone Defects - on the Experience of Two Month Follow Up - Školoudík, Lukáš; Chrobok, Viktor; Kočí, Zuzana; Popelář, Jiří; Syka, Josef; Laco, Jan; Filipová, Alžběta; Syková, Eva; Filip, Stanislav (Stem cell reviews and reports, 2018)
Temporal bone reconstruction is a persisting problem following middle ear cholesteatoma surgery. Seeking to advance the clinical transfer of stem cell therapy we attempted the reconstruction of temporal bone using a composite bioartificial graft based on a hydroxyapatite bone scaffold combined with human bone marrow-derived mesenchymal stromal cells (hBM-MSCs). The aim of this study was to evaluate the effect of the combined biomaterial on the healing of postoperative temporal bone defects and the preservation of physiological hearing functions in a guinea pig model. The treatment's effect could be observed at 1 and 2 months after implantation of the biomaterial, as opposed to the control group. The clinical evaluation of our results included animal survival, clinical signs of an inflammatory response, and exploration of the tympanic bulla. Osteogenesis, angiogenesis, and inflammation were evaluated by histopathological analyses, whereas hBM-MSCs survival was evaluated by immunofluorescence assays. Hearing capacity was evaluated by objective audiometric methods, i.e. auditory brainstem responses and otoacoustic emission. Our study shows that hBM-MSCs, in combination with hydroxyapatite scaffolds, improves the repair of bone defects providing a safe and effective alternative in their treatment following middle ear surgery due to cholesteatoma.
Keywords: cholesteatom středního ucha; Mesenchymal stromal cells; Cholesteatoma; spánková kost; Guinea Pigs; Scaffold; Hearing; mastoidektomie; heterografty; Mesenchymal Stem Cell Transplantation; Ear function; Cholesteatoma, Middle Ear; obnova funkce; Disease Models, Animal; mužské pohlaví; Temporal Bone; sluch; transplantace mezenchymálních kmenových buněk; Postoperative Complications; Osteogenesis; morčata; Mastoidectomy; osteogeneze; modely nemocí na zvířatech; zvířata; Humans; Recovery of Function; Temporal bone; Heterografts; pooperační komplikace; lidé; Male; Animals